Attori italiani alla corte della zarina Anna Ioannovna (1731-1738) - PIERONI, ALICE (Premio Ricerca «Città di Firenze», 2017)
As in a journey back in time, the stages of the first tournées of Italian actors in Russia in the 18th Century are retraced. By studying the translations of comedies and musical interludes, staged in St. Petersburg from 1731 to 1738, the practices of the first Italians who trod the stages of Tsarina Anna Ioannovna are rediscovered. Through the translation of the repertoire that has come down to us, the author reconstructs the traces of the Commedia dell'Arte and of the life and works of a handful of interpreters ready to face dangerous journeys in order to obtain gains and honors. The research, conducted on printed documents and primary archival sources, also based on the previous studies of Starikova and Ferrazzi, devotes particular attention to the biographies of the interpreters.